2011
DOI: 10.1097/ta.0b013e3182396320
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Posttraumatic Equinus Deformity and Concomitant Soft Tissue Defects of the Heel

Abstract: This study showed that posttraumatic equinus deformity accompanied by soft tissue defect of the heel can be treated effectively with Achilles tendon lengthening, reversed sural fasciocutaneous island flap transfer, and a hinged Ilizarov technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…However, the drawbacks of this technique including long operation time, donor site morbidity, and high technical requirement should not be ignored. Also, distraction osteogenesis beneath a free ap would compromise the vascularized tissue [13,14]. Therefore, instead of a free ap, we performed perforator artery pedicled neurotrophic ap, which is simpler and more e cient, for covering massive soft tissue defects.…”
Section: Discussionmentioning
confidence: 99%
“…However, the drawbacks of this technique including long operation time, donor site morbidity, and high technical requirement should not be ignored. Also, distraction osteogenesis beneath a free ap would compromise the vascularized tissue [13,14]. Therefore, instead of a free ap, we performed perforator artery pedicled neurotrophic ap, which is simpler and more e cient, for covering massive soft tissue defects.…”
Section: Discussionmentioning
confidence: 99%
“…In most previous studies on the treatment of equinus deformities, an Ilizarov external fixator was applied in combination with various open procedures. Therefore, it has been difficult to assess how much correction can be achieved with an Ilizarov external fixator alone (11,(24)(25)(26)(27). To our knowledge, only 4 studies have been published on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, an Ilizarov external fixator with the concept of distraction histogenesis has been used as a less-invasive attempt to correct equinus deformities (19)(20)(21)(22)(23). Most of the existing studies have reported the use of an Ilizarov external fixator combined with open procedures such as soft tissue release (11,(24)(25)(26)(27). Experience with correction of equinus deformities using an Ilizarov external fixator alone without adjunctive soft tissue procedures is limited.…”
mentioning
confidence: 99%
“…3,22,27,33 Arthrodesis with deformity correction usually involves extensive dissection of soft tissue, multiple osteotomies removal of large bone wedges, with increased risk of skin and bone necrosis and/or infection, 10,24,25,27 as well as excessive shortening of the foot and limb, leading to imbalance on the contralateral side. 2,3,5,20,25 Stiff equinovarus deformities (ECDs) of the foot are mostly caused by neglected trauma, 14,29 burns, 19,27 compartment syndrome of the leg, 5,14,16 peripheral nerve injury, 31 and central nervous system lesions. 2,23,26,30 These cosmetically challenging and functionally incapacitating deformities are common in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…1,6,25 Poor skin quality/multiple scars, joint stiffness secondary to arthrofibrosis, shortening of the foot, claw toes, and neglected or mistreated childhood osteoarticular deformities can further complicate efforts to achieve a plantigrade foot. 1,2,3,5,[10][11][12][13]18,19,22,[23][24][25][26]28,29 Gradual and progressive correction of these severe deformities, using the distraction-osteogenesis principle proposed by Ilizarov 21 delivered through an external circular fixator, is a less invasive, yet highly effective, alternative in such cases. 5,12,13,15 According to Ilizarov, both soft tissue and bone can grow in response to gradual progressive controlled distraction force.…”
Section: Introductionmentioning
confidence: 99%